2014
DOI: 10.1103/physrevb.89.075301
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous scaling of spin accumulation in ferromagnetic tunnel devices with silicon and germanium

Abstract: Anomalous scaling of spin accumulation in ferromagnetic tunnel devices with silicon and germanium Sharma, S.; Spiesser, A.; Dash, S.P.; Iba, S.; Watanabe, S.; Wees, B.J. van; Saito, H.; Yuasa, S.; Jansen, R. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
55
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 51 publications
4
55
2
Order By: Relevance
“…On the other hand, spin lifetimes in metals obtained by 3T measurements are significantly longer than theoretically predicted 17 . Several experiments also proposed an enhancement 15,18 or inversion 8 of the 3T spin signal, whereas multiple control experiments rule out any enhancement due to interface states 6,16,19 . Therefore, it is required to understand the contributing factors in both techniques by performing experiments in the NL and 3T configuration using the same magnetic tunnel contacts.…”
mentioning
confidence: 99%
“…On the other hand, spin lifetimes in metals obtained by 3T measurements are significantly longer than theoretically predicted 17 . Several experiments also proposed an enhancement 15,18 or inversion 8 of the 3T spin signal, whereas multiple control experiments rule out any enhancement due to interface states 6,16,19 . Therefore, it is required to understand the contributing factors in both techniques by performing experiments in the NL and 3T configuration using the same magnetic tunnel contacts.…”
mentioning
confidence: 99%
“…As noted earlier, previous work has suggested that anomalously large 3T spin signals may result from spin accumulation in localized interface states rather than in the semiconductor channel itself 52 , anomalous scaling 53 or magnetic field-modulated resonant tunnelling 54 . Further work is necessary to elucidate the origin of these large signals.…”
Section: Resultsmentioning
confidence: 93%
“…The large discrepancy may be attributed to leakage currents, an overestimate of the actual tunnel contact area due to inhomogeneous tunnelling or an overestimate of the tunnelling spin polarization. Previous work has suggested that spin signals much larger than those predicted by theory may be due to spurious effects such as spin accumulation in localized interface states rather than in the semiconductor channel itself 52 , anomalous scaling 53 or magnetic field-modulated resonant tunnelling 54 . The fact that our experimental value is smaller than that predicted provides some evidence that such effects do not play a significant role in our devices.…”
Section: Resultsmentioning
confidence: 99%
“…However, the resulting enhancement of the Hanle signal is not sufficiently large to explain recent experiments in which Hanle signals that scale with the tunnel resistance and are many orders of magnitude larger than predicted by theory are observed [38][39][40][41][42][43][44], as recently reviewed [27,45]. It would require α ≪ 1 by several orders of magnitude.…”
mentioning
confidence: 89%